The sexual and reproductive health needs and preferences of youths in sub-Saharan Africa: A meta-synthesis. - Victoria Kalu Uka; Helen White; Debbie M Smith (PLoS ONE)
The sexual and reproductive health (SRH) needs of youths in sub-Saharan Africa are not being fully met, as evidenced by high rates of unintended pregnancies and sexually transmitted infections in this population. Understanding service needs and preferences of sub-Saharan African youths aged 10-24 years is critical for improving access and SRH outcomes and the focus of this systematic review of qualitative research. Four databases were searched with key words to identify relevant studies, supplemented by citation search, with an update in June 2023. The eligibility criteria were clear and developed a priori. Twenty included studies from seven countries underwent quality appraisal using the Critical Appraisal Skills Programme (CASP). A meta-ethnographic approach was used to synthesise concepts across studies by the researchers. Four key themes were generated: information needs; service needs; social needs; and delivery preferences. Information needs encompassed desires for age-appropriate education on contraception, safer sex, bodily changes, and healthy relationships to fill knowledge gaps. Social needs consisted of life skills training, vocational development, substance use rehabilitation, and support systems to foster healthy behaviours. Service needs included accessible youth-friendly sexual health services, preventative care, sexually transmitted Infections (STI) management, and contraception; and delivery preferences including competent providers who maintain privacy and confidentiality, convenient youth-oriented settings, free or low-cost provisions, and youth involvement in service design. In conclusion, the identified themes emphasise the diverse nature of SRH needs and preferences among sub-Saharan African youths. Insights from their unique priorities and unmet needs inform policy development and intervention strategies. Tailored awareness campaigns, youth-centred training for providers, youth-friendly and confidential SRH models, comprehensive education, and engaging youth in developing relevant solutions may improve acceptability, access, and health outcomes. These efforts could address barriers around stigma, costs, and lack of knowledge, contributing to enhanced SRH and wellbeing. Fulfilling youth SRH needs in sub-Saharan Africa requires commitment across sectors to evidence-based, youth-focused strategies placing their perspectives at the centre.